CONTESTING AUTHORITY DISCOURSES IN DEFINING RELATIONS BETWEEN INDONESIA AND MALAYSIA: A CASE STUDY IN THE KALIMANTAN BORDER AREAS (Journal of International Studies, 2022)
This article discusses and analyses relations between Indonesia and Malaysia from the relational dynamism between people and the state. Theoretically, the relations can be narrated through identity formation approach in the context of ‘authoritative-defined social reality’ and ‘everyday-defined social reality’. The reality of Indonesia-Malaysia relations in the last twenty-five years was very much defined by authoritative or elitist views, which have dominated and controlled the everyday discourses. However, elitist groups’ reality-defined perspective does not paint the whole picture of relations. This article argues that it is crucial to analyse the relations in the context of ‘everyday-defined social reality’ especially from the common people’s perspective such as workers, traders, activists, novelists, religious groups, artists, and families, who experience the reality of the relations. This ‘social reality’ can be observed in the dynamism of cross border relation between people-to-people, as has been shown in our case studies, in the border areas of Kalimantan Barat and Sarawak as well as Kalimantan Utara-Sabah. It shows complex but generally positive pictures in understanding relations between two countries. It is therefore expected that the awareness and understanding of this ‘everyday-reality’ can contribute to a better understanding of relations between the two countries.